(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Today’s wireless networks allocate radio resources to users based on the Orthogonal Multiple Access (OMA) principle. However, as the number of users increases, OMA based approaches may not meet the stringent emerging requirements including very high spectral efficiency, very low latency, and massive device connectivity. Non-Orthogonal multiple access (NOMA) principle emerges as a solution to improve the spectral efficiency while allowing some degree of multiple access interference at receivers. NOMA is fundamentally different than orthogonal multiple access schemes which provide orthogonal access to the users either in time, frequency, code or space. In NOMA, each user operates in the same band and at the same time where they are distinguished by their power levels. NOMA uses superposition coding at the transmitter such that the successive interference cancellation (SIC) receiver can separate the users both in the uplink and in the downlink channels. This paper analyzes the spectral efficiency of Filter Bank Multiple Carrier (FBMC) and Universal Filter Multiple Carrier(UFMC) Modulation Schemes with NOMA while considering Orthogonal Quadrature Amplitude Modulation (OQAM) as the modulation scheme and NOMA as the multiple access scheme.